COMPUTATION OF THE AVERAGE WOOD TEMPERATURE AND THE RATE OF ITS CHANGE DURING UNILATERAL HEATING OF FLAT SPRUCE DETAILS BEFORE THEIR BENDING (Innovation in Woodworking Industry and Engineering design, 2026)
An approach for the computation of the average mass temperature of the wood and the rate of its change during unilateral heating of flat wood details aimed at their plasticizing in the production of curved outside parts for corpses of stringed music instruments, has been suggested. The approach is based on the numerical integration of the solutions of a linear model for the calculation of the non-stationary 1D temperature distribution along the thickness of subjected to unilateral heating flat wood details.